Purification of Hodgkin's Disease Tumor-Associated Antigens - Katz, David H. (National Academy of Sciences, 1973)
Two antigens that exist in high frequency in tumor tissues of patients with Hodgkin's disease have been obtained in relatively concentrated form. Extracts of Hodgkin's spleen tumor tissue, when subjected to chromatography on Sephadex G-200, separate into three major protein peaks of which only the first (peak I) possesses the predominant antigenic activities associated with the disease. Antigenic analysis performed with hyperimmune rabbit antisera obtained after repeated immunizations with peak I proteins demonstrated that this fraction contained both F and S antigens associated with Hodgkin's disease and small contaminant amounts of an antigen associated with normal lymphocytes. The tissue distribution patterns of the Hodgkin's disease tumor-associated antigens suggest that they both originate in lymphoid tissues and that the F antigen may represent a product of reactive lymphocytes while the S antigen may be a dedifferentiation antigen expressed in very immature lymphocytes. IMAGES: